THE PROFILE OF BILINGUAL EDUCATION AT DYATMIKA KINDERGARTEN - WIDHIASIH, LUH KETUT SRI (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Widhiasih, Luh Ketut Sri (2012). The Profile of Bilingual Education at Dyatmika Kindergarten. Tesis, Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Pendidikan Ganesha Singaraja. This thesis has been examined and corrected by Supervisor I: Prof. Dr. Putu Kerti Nitiasih, M.A. and Supervisor II: Dra. Luh Putu Artini, M.A. Ph.D. This study was a phenomenology research involving descriptive-qualitative design. This study aimed at identifying profile of bilingual education at Dyatmika Kindergarten. This study was conducted in Dyatmika Kindergarten. The present study was conducted to the school personnel and community including the headmaster, four teachers and some studentsâ parents of Dyatmika Kindergarten. The data obtained in this study are qualitative data. The qualitative data were obtained from guided interview in the form of some related information, observation and document analysis. The data were gained through several research instruments, such as researcher as key instrument, list of guided interview questions, checklist, and observation sheet. The result of interview, observation, and document analysis data were analyzed descriptively using Interactive Model. This study found that Dyatmika Kindergarten had completely fulfilled the criteria of a good bilingual school, such as having and achieving clear school goals, having safe school climate, integrating bilingual program to school community, providing leadership and support for bilingual program, having quality personnel, having good relationship with parents and communities of the students, having quality curriculum, and instructions. Based on the result, Dyatmika Kindergarten could be proposed to be a model for other bilingual kindergarten. Â  Keywords: profile, bilingual education, bilingual kindergartenÂ ABSTRAK Widhiasih, Luh Ketut Sri (2012). Profil Pendidikan Dwi-bahasa di Taman Kanak-kanak Dyatmika. Tesis, Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Pendidikan Ganesha Singaraja. Tesis ini telah diperiksa dan dikoreksi oleh Pembimbing I: Prof. Dr. Putu Kerti Nitiasih, M.A. dan Pembimbing II: Dra. Luh Putu Artini, M.A. Ph.D. Penelitian fenomenologi yang menggunakan rancangan deskriptif kualitatif ini bertujuan untuk mengidentifikasi profil pendidikan dwi-bahasa di Taman Kanak-kanak Dyatmika. Subjek penelitian ini adalah warga dan komunitas sekolah yang mencakup kepala sekolah, empat guru, dan beberapa orang tua siswa Taman Kanak-Kanak Dyatmika. Data yang diperoleh pada penelitian ini berjenis data kualitatif. Data kualitatif diperoleh dari wawancara terstruktur, observasi, dan analisis dokumen. Data diperoleh dengan menggunakan peneliti sebagai instrument kunci dan beberapa instrumen penelitian lain seperti lembar daftar pertanyaan wawancara terstruktur, checklist, dan lembar observasi. Hasil wawancara terstruktur, observasi dan analisis dokumen dianalisis secara deskriptif menggunakan Model Interaktif. Hasil penelitian menunjukkan bahwa Taman Kanak-kanak Dyatmika telah dengan lengkap memenuhi kriteria-kriteria sebuah sekolah dwi-bahasa yang bagus, seperti memiliki tujuan sekolah yang jelas dan tercapai, memiliki iklim sekolah yang aman, mengintegrasikan program dwi bahasa dengan komunitas sekolah, menyediakan sistem kepemimpinan dan dukunganÂ  untuk program dwi bahasa, memiliki personil berkualitas, memiliki hubungan yang baik dengan orang tua dan komunitas sekolah, memiliki kurikulum berkualitas dan instructions berkualitas. Berdasarkan temuan, Taman Kanak-kanak Dyatmika bisa diajukan sebagai sekolah model bagi taman kanak-kanak dwi-bahasa lainnya. Â  Kata kunci: profil, pendidikan dwi-bahasa, taman kanak-kanak dwi-bahasa